Perceived Stress and Molecular Bacterial Vaginosis in the National Institutes of Health Longitudinal Study of Vaginal Flora. Issue 11 (19th May 2021) - Turpin, Rodman; Slopen, Natalie; Borgogna, Joanna-Lynn C; Yeoman, Carl J; He, Xin; Miller, Ryan S; Klebanoff, Mark A; Ravel, Jacques; Brotman, Rebecca M
Abstract: Vaginal microbiota provide the first line of defense against urogenital infections primarily through protective actions of Lactobacillus species Perceived stress increases susceptibility to infection through several mechanisms, including suppression of immune function. We investigated whether stress was associated with deleterious changes to vaginal bacterial composition in a subsample of 572 women in the Longitudinal Study of Vaginal Flora, sampled from 1999 through 2002. Using Cox proportional hazards models, both unadjusted and adjusted for sociodemographic factors and sexual behaviors, we found that participants who exhibited a 5-unit-increase in Cohen's Perceived Stress Scale had greater risk (adjusted hazard ratio (HR) = 1.40, 95% confidence interval (CI): 1.13, 1.74) of developing molecular bacterial vaginosis (BV), a state with low Lactobacillus abundance and diverse anaerobic bacteria. A 5-unit increase in stress score was also associated with greater risks of transitioning from the L. iners -dominated community state type (26% higher) to molecular-BV (adjusted HR = 1.26, 95% CI: 1.01, 1.56) or maintaining molecular-BV from baseline (adjusted HR = 1.23, 95% CI: 1.01, 1.47). Inversely, women with baseline molecular-BV reporting a 5-unit stress increase were less likely to transition to microbiota dominated by L. crispatus, L. gasseri, or L. jensenii (adjusted HR = 0.81, 95% CI: 0.68, 0.99). These findings suggest that psychosocial stress is associated with vaginal microbiota composition, inviting a more mechanistic exploration of the relationship between psychosocial stress and molecular-BV.